Image-Guided Intensity-Modulated Radiation Therapy for IgG4-Related Ophthalmic Disease - Rachel A. Sabol; Virginia Bubenzer; Krzysztof Moroz; Shams Halat; Audrey Dang; Keith Ferdinand; Angela Traylor; Carol Boyd; Kendra Harris (Case Reports in Ophthalmological Medicine)
Background. IgG4-related ophthalmic disease is a rare, newly recognized entity with high failure rates on first-line therapy of systemic corticosteroids and no other proven management options. Case Presentation. Here, we present the clinical course of a patient with IgG4 ophthalmic disease who achieved a favorable response from radiotherapy. Our patient initially presented with a history of recurrent painful flares of orbital inflammation, a pathologic diagnosis follicular lymphoid hyperplasia from a right lacrimal gland biopsy, and MRI imaging noting expansion of the lateral rectus muscle of the right eye. Initial treatment with dacryoadenectomy and multiple courses of corticosteroids failed to keep his symptoms at bay. Further evaluation revealed florid IgG4 staining. In this context, he was evaluated for image-guided intensity-modulated radiotherapy (IG-IMRT) to the orbit to 20 Gy in 10 fractions. His ophthalmic symptoms resolved. Conclusions. This treatment experience suggests radiotherapy may be a favorable option for symptom relief in patients with IgG4-related ophthalmic disease not controlled by corticosteroids.